A literature review on learning styles in technical, graduation and specialization courses and on the impacts of emergency remote education - Assunção, Marcelo Teodoro (2020)
The way in which each person learns throughout his life is influenced by the individual's own characteristics, external factors related to the environment in which he lives and his experiences. Each individual presents their own preferences on how to receive and process information, consolidating, thus, their learning on a given subject. These different preferential forms are defined as Learning Styles. The knowledge of the styles of his students allows the teacher to adopt strategies that promote improvements in the performance of the whole class, directing the content according to the preferences of his students. The importance of teachers' practices in teaching gained even more importance in 2020 due to COVID-19 pandemic. As classroom teaching activities were suspended, institutions adopted Emergency Remote Teaching. It was necessary to quickly adapt education professionals to the use of Digital Information and Communication Technologies, thus characterizing a great challenge for teachers in pedagogical practices. Within this context, this work aims to review the literature on the Learning Styles of students in technical education, graduation and specialization courses, both in person and at distance, according to Felder and Silverman Learning Styles Index, and also to present investigations and reports on the impacts of Emergency Remote Education on teachers' lives.